2020
DOI: 10.1039/d0sc03290e
|View full text |Cite
|
Sign up to set email alerts
|

Coordinative-to-covalent transformation, isomerization dynamics, and logic gate application of dithienylethene based photochromic cages

Abstract: Photochromic coordinative cages containing dynamic C=N imine bonds are assembled from dithienylethene-based aldehyde and tris-amine precursors via metallo-component self-assembly. The resulting metal-templated cages are then reduced and demetalated into pure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Rare-earth metals can also be used to construct SCCs. In 2018, Cai et al [46] reported the construction of a chiral diarylethene-based metallacage via Eu coordination and studied its photochromic behavior. As shown in Figure 14, by reacting of the diarylethene-containing chiral ligand 39 with Eu(ClO 4 ) 3 •6H 2 O in a 3:2 ratio in CH 3 CN, the Eu 2 L 3 helicate 40o was obtained quantitatively, which was well characterized with NMR and ESI-TOF-MS spectra.…”
Section: Figure 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Rare-earth metals can also be used to construct SCCs. In 2018, Cai et al [46] reported the construction of a chiral diarylethene-based metallacage via Eu coordination and studied its photochromic behavior. As shown in Figure 14, by reacting of the diarylethene-containing chiral ligand 39 with Eu(ClO 4 ) 3 •6H 2 O in a 3:2 ratio in CH 3 CN, the Eu 2 L 3 helicate 40o was obtained quantitatively, which was well characterized with NMR and ESI-TOF-MS spectra.…”
Section: Figure 12mentioning
confidence: 99%
“…As shown in Figure 15, the metallacages 44o-46o were Excitation and emission spectra of the helicates. This figure is used with permission from Cai et al [46] . obtained through the reaction of 41o, tris(2-aminoethyl) amine (42) and Zn(OTf) 2 or Cd(OTf) 2 in CH 3 CN/CHCl 3 .…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16‐18 ] Generally, metal/ligand building blocks with specific angularity are used to construct topologically simple structures such as rings and cages with high symmetries. [ 19‐26 ] Low‐symmetry architectures such as crowns and bowls are difficult to design and synthesis. [ 27‐29 ] Only a few coordination complexes could be described as molecular bowls.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…7,8 Inspired by this, many unusual metal complexes which can be used to fix CO 2 through binding with carbonate have been reported. 9–13 Coordination-directed self-assembly has been proven to be an effective approach toward the predictable construction of multicomponent artificial hosts, 14–77 where enhanced guest reactivity, 73,74,78–87 stabilization of metastable species, 88–90 and unusual reaction pathways 78,91–94 have been realized. While atmospheric CO 2 sequestration by selective binding of carbonate with coordination hosts has already been reported, 95–102 adaptive coordination hosts that contain multiple active metal sites and can reversibly encapsulate and release the carbonate are still rare.…”
Section: Introductionmentioning
confidence: 99%